ChemInform Abstract: From Enantiopure Hydroxyaldehydes to Complex Heterocyclic Scaffolds: Development of Domino Petasis/Diels—Alder and Cross‐Metathesis/Michael Addition Reactions. Issue 11 (March 2015) - Cannillo, Alexandre; Norsikian, Stephanie; Tran Huu Dau, Marie‐Elise; Retailleau, Pascal; Iorga, Bogdan I.; Beau, Jean‐Marie
Abstract A sequence combining Petasis and Diels—Alder reactions gives access to hexahydroisoindole scaffolds in a one‐step procedure.